Oil Price Volatility and Stock Market Returns in an Emerging Economy: Evidence from Nigeria - Ikponmwosa Michael Igbinovia; Eghosa Lawson Igbinovia (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2019)
The study examines the reaction of the Nigerian stock market to fluctuations in the  mainstay of the Nigerian economy. Using time series data sourced from OPEC website and the Central Bank of Nigeria (CBN) Statistical Bulletin, we investigate the effect of oil price volatility on stock market returns in Nigeria during the period 1981 to 2017. Cointegration test established the long run relationship between variables, while, the Error Correction Model (ECM) and Pair-Wise Granger Causality test were used to ascertain the short run dynamics and the direction of causality between the variables of interest. The findings reveal among other things that Oil Price Volatility (OPV) has a non-significant positive effect on Stock Market Return (SMR) both in the short and long run period. Exchange Rate (EXR) and Interest rate (INT) were significant variables that influence stock market return in Nigeria during the period under review